1993
DOI: 10.1093/ije/22.5.761
|View full text |Cite
|
Sign up to set email alerts
|

Serum Beta-Carotene and Antioxidant Micronutrients in Children with Cancer

Abstract: Serum antioxidant vitamins A (retinol) and E (alpha-tocopherol), beta-carotene, zinc and selenium for 418 children with newly diagnosed malignancy were compared with those of 632 cancer-free controls. Incident cancer cases and controls were 1-16 years old and recruited in 1986-1989. Age- and sex-adjusted serum concentrations of retinol, beta-carotene and alpha-tocopherol were significantly inversely associated with cancer. In similar models, the odds ratio (OR) comparing the highest with the lowest quintile wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…These results were also confirmed by Zuo et al and Unal et al, who found decreased zinc levels in serum of leukemic patients (Zuo et al, 2006) and in serum of Hodgkin's disease patients, respectively (Unal et al, 2001). Moreover, decreased blood levels of antioxidants (i.e., retinol, α-tocopherol, and β-carotene) and zinc were found in childhood malignancies (Malvy et al, 1993(Malvy et al, , 1997, which could be one of the negative effects of zinc-metabolism alterations. Zinc deficiency has also been associated with oxidative stress (OS) (Eide, 2011) and esophageal, head and neck cancer, and prostate and other cancer types, especially in their development and progression (Franklin and Costello, 2007;Hogstrand et al, 2009;Ostrakhovitch, 2011;Fukada et al, 2011;Pedersen et al, 2009).…”
Section: S Krizkova Et Alsupporting
confidence: 76%
“…These results were also confirmed by Zuo et al and Unal et al, who found decreased zinc levels in serum of leukemic patients (Zuo et al, 2006) and in serum of Hodgkin's disease patients, respectively (Unal et al, 2001). Moreover, decreased blood levels of antioxidants (i.e., retinol, α-tocopherol, and β-carotene) and zinc were found in childhood malignancies (Malvy et al, 1993(Malvy et al, , 1997, which could be one of the negative effects of zinc-metabolism alterations. Zinc deficiency has also been associated with oxidative stress (OS) (Eide, 2011) and esophageal, head and neck cancer, and prostate and other cancer types, especially in their development and progression (Franklin and Costello, 2007;Hogstrand et al, 2009;Ostrakhovitch, 2011;Fukada et al, 2011;Pedersen et al, 2009).…”
Section: S Krizkova Et Alsupporting
confidence: 76%
“…A separate high-performance liquid chromatography assay comprising an isocratic system using silica gel (adsorption) as the stationary phase was used for retinol, alpha-tocopherol, and beta-carotene, as described previously [3,5]. Results for alpha-tocopherol were also expressed as ratio of serum vitamin E to cholesterol.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore investigated whether abnormal breakdown of antioxidants such as beta-carotene, alpha-tocopherol, zinc, and selenium occurs at the time of diagnosis and might follow the conditioning therapy in certain groups of children with cancer. The study was conducted in France as a satellite investigation of a large multicenter case-control survey designed to document the relationship between serum micronutrient values and childhood malignancy [3]. We therefore measured retinol (vitamin A), beta-carotene, alpha-tocopherol (vitamin E), cholesterol, zinc, selenium, and related proteins in serum collected from 1986 to 1989 from 170 children aged 1-16 years with newly diagnosed cancer, and from 632 healthy controls who were cancer free.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the role of antioxidants in preventing tumor progression may be crucial. Several epidemiological studies revealed significant differences in antioxidant status between healthy persons and cancer patients, which indicated disturbances in antioxidant status in cancer risk [19,21]. Follow-up prospective studies showed associations between high antioxidants/microelements level and high fruit and vegetable consumption and a lower cancer risk, e.g.…”
Section: Introductionmentioning
confidence: 99%